Fiscal redistribution in Brazil: Dynamic microsimulation, 2003-15 - Marcelo Cortes Neri; Rozane Bezerra de Siqueira; José Ricardo Bezerra Nogueira; Manuel Osorio (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
This paper assesses causes and consequences of fiscal redistribution in Brazil. The framework proposed allows evaluating in an integrated manner the impacts of government-sponsored actions in inequality and mean income changes on social welfare, addressing both static and dynamic implications. To the best of our knowledge, this is the first microsimulation attempt to gauge actual fiscal policy redistribution changes over time in Brazil. The study develops an empirical methodology that allows consistent comparisons among the years 1995, 2003, 2009, and 2015. We focus on disposable income changes between 2003 and 2015. In this period, the Gini index-based social welfare grew 4.86 per cent per year; that is, higher than the growth rates associated with both initial income (4.36 per cent) and final income (4.47 per cent), but not with gross income (4.91 per cent). The results suggest that official cash transfers accelerated the growth of social welfare while direct and indirect tax changes operated in the opposite direction. The model outcomes allow assessing the role played by specific fiscal instruments among various taxes and cash transfer programmes. The family grant programme was the best-targeted action in the 2003-15 period. Its contribution to the rise of social welfare is 2.7 times the contribution to the rise of mean income. If one compares family grant poverty impacts with the second best targeted cash transfer programme, each monetary unit spent generated a 119.73 per cent higher impact.
Keywords: C63; H23; I32; I38; 330; fiscal redistribution; income inequality; taxes and transfers